Moderna Museet Projekt : Maria Lindberg. - Elliot, David; Moderna Museet, Stockholm; Lind, Maria (Stockholm : Moderna museet, 1998)
Lindberg, Maria
Moderna Museet Projekt: Maria Lindberg, Moderna Museet, Stockholm, 14/2 - 19/4 1998
kunstcatalogus